A study of cyberstander reactions under community-related influence: When gender complicates matters. (February 2021) - Stanciu, Dorin; Chis, Alexandra
Abstract: Past research provided consistent evidence regarding the influence of the community context on the individuals' behavior. However, much less is known about the translation of this effect into cyberspace. Hence, our study investigated three main community-level factors ( i.e., 'community rules', 'community reactions', and 'informational framing') that have been scarcely researched to date and which may impact the behavior of those witnessing a cyberbullying incident without participating directly to it (cyberstanders). Additionally, we included gender in our study because it was indicated by previous studies as a relevant moderator across the entire spectrum of the cyberbullying research. Our main research question focused on investigating whether and to what extent these four major factors and their potential interactions have a relevant influence on cyberstanders' reactions. The participants ( N = 1841) were randomly assigned online to eight between-groups experimental conditions, in a 2 × 2 x 2 × 2 factorial design. The measurement instrument was a self-reported online questionnaire measuring the reaction to witnessing cyberbullying behavior. Our analysis found significant effects of community rules, framing, and gender on the reaction of cyberbullying, but there was no significant effect of community rules. While specific combinations of community-related factors had a statistically significant effect on cyberstanders' response, their effect sizes were small. We concluded that the impact of online community environmental features on individuals' responses to cyberbullying is limited and can vary as a function of gender. Our results indicated that social conformity might be lower online than suggested by the research in offline contexts. Furthermore, the impact of gender on certain behavioral outcomes transcends the offline environment and manifests also within the virtual environment. Future research should continue and refine the study of environmental factors on cyberstander reaction. Online communities might use framing and awareness-raising processes to increasing active resistance to cyberbullying. Highlights: Normative and informative community-related factors influence cyberstander reaction. Cyberstanders' gender is a differentiating factor for the reaction to cyberbullying. Framing and formal norms influence cyberstander reaction. Factors' interactions should be considered when interpreting and attributing effects. Awareness-raising and framing can be used to prompt active resistance to cyberbullying.